MEKANISME KERJASAMA PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN (PPATK) DAN INSTANSI TERKAIT DALAM PENYELIDIKAN PENYIDIKAN TINDAK PIDANA PENCUCIAN UANG - Putu Kartika Sastra; Gde Made Swardhana; Ida Bagus Surya Darmajaya (Kertha Negara : Journal Ilmu Hukum, 2013)
In Article 40 of the Regulation of the President of the Republic Indonesia No. 50of 2011 Article 2 paragraph (1) assign tasks to PPATK to the prevention and combatingof money laundering. Of this task can take action PPATK suspension of all or part oftransactions suspected of being proceeds of crime.Money laundering generally starts from the PPATK provide FinancialIntelligence to law enforcement authorities and ask for the development of inquiries andinvestigations that have been conducted by investigators predicate offenses. Is aninvestigator of the predicate offense is an officer of the agency by law is given theauthority to conduct an investigation, the Indonesian National Police, the AttorneyGeneral, the Corruption Eradication Commission (KPK), the National NarcoticsAgency (BNN), and the Directorate General for Taxation and Directorate General ofCustoms and Excise, Ministry of Finance of the Republic of Indonesia.